In vivo formation of complex microvessels lined by human endothelial cells in an immunodeficient mouse - Schechner, Jeffrey S. (The National Academy of Sciences, 2000)
We have identified conditions for forming cultured human umbilical vein endothelial cells (HUVEC) into tubes within a three-dimensional gel that on implantation into immunoincompetent mice undergo remodeling into complex microvessels lined by human endothelium. HUVEC suspended in mixed collagen/fibronectin gels organize into cords with early lumena by 24 h and then apoptose. Twenty-hour constructs, s.c. implanted in immunodeficient mice, display HUVEC-lined thin-walled microvessels within the gel 31 days after implantation. Retroviral-mediated overexpression of a caspase-resistant Bcl-2 protein delays HUVEC apoptosis in vitro for over 7 days. Bcl-2-transduced HUVEC produce an increased density of HUVEC-lined perfused microvessels in vivo compared with untransduced or control-transduced HUVEC. Remarkably, Bcl-2- but not control-transduced HUVEC recruit an ingrowth of perivascular smooth-muscle α-actin-expressing mouse cells at 31 days, which organize by 60 days into HUVEC-lined multilayered structures resembling true microvessels. This system provides an in vivo model for dissecting mechanisms of microvascular remodeling by using genetically modified endothelium. Incorporation of such human endothelial-lined microvessels into engineered synthetic skin may improve graft viability, especially in recipients with impaired angiogenesis.